Application of Al2O3:C+fibre dosimeters for 290 MeV/n carbon therapeutic beam dosimetry. (October 2015) - Nascimento, L.F.; Vanhavere, F.; Kodaira, S.; Kitamura, H.; Verellen, D.; De Deene, Y.
Abstract: The capability of radioluminescence (RL) dosimeters composed of carbon-doped aluminium oxide (Al2 O3 :C) detectors+optical fibre has been verified for absorbed dose-rate measurements during carbon radiotherapy. The RL signals from two separate Al2 O3 :C detectors (single crystal 'CG' and droplet 'P1') have been systematically measured and compared along the Bragg-curve and Spread-Out Bragg-Peak of 290 MeV/n carbon beams in the water. The absorbed dose response was assessed for the range of 0.5–10 Gy. For doses up to 6 Gy, we observed a linear response for both types of detectors, while for higher doses CG presented a more prominent supraliearity than P1. The RL response for low-LET protons in the entrance from the curve was found to closely resemble that observed for a clinical 6 MV X-ray beam, while it was found that P1 has a better agreement with the reference data from standard ionization chamber than CG. We observed a significant decrease in luminescence efficiency with LET in the Bragg peak region. The Al2 O3 :C RL luminescence efficiency differs from Al2 O3 :C OSL results, which implies that the signal can be corrected for LET dependency to match the correct SOBP and Bragg Peak. Highlights: Radioluminescence (RL) real time signal from Al2 O3 :C+fibre probes. Irradiations with 290 MeV/n Carbon. Two types of detectors were tested: droplet and single crystal. Luminescence efficiencies for each probe were compared with 6 MV photons. Bragg Peak and SOBP are obtained. Luminescence efficiencies for Optically Stimulated Luminescence (OSL) and RL are compared for Al2 O3 :C.